(untitled) (Academicia Review-A Multidisciplinary Online Journal, 2026)
Neurofibromatosis type I (NF1) is a genetically determined neurocutaneous disorder characterized by significant clinical variability and a high incidence of neurological complications. This study aimed to analyze the spectrum of neurological disorders associated with NF1 and to evaluate outcomes of surgical treatment for tumors affecting the peripheral and central nervous systems. A total of 112 patients aged 14–62 years underwent comprehensive evaluation. Spinal and spinal cord tumors were identified in 58% of cases, while clinically significant neural compression occurred in 16%. Surgical treatment was performed in 38 patients with symptomatic disease. Postoperative neurological improvement was achieved in 71% of cases. These findings highlight the importance of early diagnosis and timely surgical intervention in progressive NF1-related neurological complications